Tuberosciponoceras: a new dimorphic ammonoid genus from the Upper Albian of Patagonia, Argentina - Medina, Francisco A. (2007)
Tuberosciponoceras insolitum n. gen., n. sp. is a single dimorphic species in the Upper Albian of the Austrat Basin, southern Patagonia. The short-lived genus was characterized by distinct ventral tubercles on all ribs and a deep, trifid internal lobe.